Pengaruh Pengungkapan ESG, Biaya Lingkungan, dan Green Accounting Terhadap Kinerja Keuangan - Febrianti, Salwa Nayla; Machdar, Nera Marinda (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the impact of ESG disclosure, environmental costs, and green accounting on corporate financial performance. This research is motivated by the increasing demands for sustainability in business, yet companies' consistency in implementing ESG principles remains relatively low, particularly in the manufacturing sector, which has a significant environmental impact. The results show that ESG disclosure is associated with the possibility of increased profitability through increased legitimacy and stakeholder trust. Environmental costs have two perspectives: some studies find a negative impact on financial performance due to increased cost burdens, while others view them as a long-term investment that can improve efficiency. Green accounting is associated with increased resource utilization effectiveness and enhanced corporate competitiveness. Based on the literature review, all three sustainability variables have a significant relationship with financial performance, although empirical research results show discrepancies. This study provides an overview of the importance of implementing sustainability practices in improving the financial performance of manufacturing companies in Indonesia.